Aluminum-lithium alloy and preparation method thereof
By using Sc elements to replace Zr in aluminum-lithium alloys and combining specific heat treatment processes to prepare ultralight aluminum-lithium alloys with excellent mechanical properties, the shortcomings of existing aluminum-lithium alloys in terms of lightweight and strength improvement are solved.
Patent Information
- Application Number
- CN202510439060.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-04-09
AI Technical Summary
The existing aluminum-lithium alloys have shortcomings in lightweighting and strength improvement, especially when they contain high-density element Zr, the overall weight reduction effect is poor, and the heat treatment method leads to poor strength and plastic matching.
By rationally designing the composition of aluminum-lithium alloy, using the rare earth element Sc instead of Zr, and controlling the content of Sc element, combining homogenization treatment, hot rolling, solid solution and aging treatment, an ultralight aluminum-lithium alloy with good strong plasticity was prepared.
The lightweight aluminum-lithium alloy is achieved, while improving its strength and mechanical properties, reducing the density to 2.47 g/cm2, the room temperature tensile strength reaches 554MPa, the elongation is 10.84%, and the overall performance is the best.
Smart Images

Figure CN119956174A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloy materials, and in particular to an aluminum-lithium alloy and a preparation method thereof. Background Art
[0002] Aluminum-lithium alloy is a lightweight alloy with excellent comprehensive performance and great development potential. Replacing ordinary aluminum alloy with it can reduce the weight of components and increase stiffness. Therefore, it is considered to be a very ideal structural material for aerospace applications in the 21st century. It also has potential application space in ships and weapons industries. At present, the aluminum-lithium alloy series successfully developed by various countries generally contain 2.3%~3% lithium. Aluminum-lithium alloys (2090, 2195, 8090) are used as secondary structural components in fighter jets and civil aircraft, including the leading edge of the wing and the brackets in the fuselage. However, aluminum-lithium alloys (2090, 2195, 8090) contain 0.1wt.%-0.12 wt.% of the high-density element Zr (6.49 g / cm 3 ), there is a problem of poor comprehensive weight reduction effect. Specifically, its comprehensive weight reduction effect is generally only 5%-7%, which is half of that of composite materials.
[0003] Aluminum-lithium alloy is a deformable aluminum alloy and a heat-treatable aluminum alloy. The main heat treatment method is solid solution plus aging treatment. Through a series of heat treatment methods, it precipitates strengthening phases and regulates the strength and toughness of the alloy. For example, the common 2195 aluminum-lithium alloy can achieve a peak stress of 550-590MPa through appropriate heat treatment methods. Many studies have shown that the main strengthening phases in aluminum-lithium alloys include T1 phase (Al2CuLi), δ′ phase (Al3Li), θ′ phase (Al2Cu), etc. Among them, the T1 phase is a close-packed hexagonal structure with the strongest strengthening effect. Therefore, in order to make the alloy have a certain strength under the premise of good plasticity, it is hoped that a large number of fine T1 phases (Al2CuLi) will be dispersed and precipitated in the alloy through heat treatment.
[0004] One of the effective ways to improve the performance of aluminum-lithium alloys is to regulate the structure through alloying. Sc is the rare earth element with the lowest density. It has the properties of transition elements, which is exactly the most effective modifier for aluminum-lithium alloys. Adding it to aluminum-lithium alloys, through homogenization annealing and hot forging deformation processing, can make the alloy precipitate small-sized, high-density and dispersed Al3Sc / Al3Sc xPhase particles can be firmly pinned on dislocations and subgrain boundaries, which can prevent the migration and merging of subgrains to stabilize the substructure. At the same time, they can increase the recrystallization temperature and have a great inhibitory effect on the recrystallization behavior of the alloy. Theoretically, in aluminum-lithium alloys, the addition of Sc elements can change the precipitation behavior of alloy precipitation phases at the component level; but in fact, the aging precipitation characteristics of Sc elements in Al-Cu-Li alloys and the mechanism of organizational regulation performance have not been fully clarified, and the optimal aging treatment process is also different.
[0005] Xing Yuhan et al. proposed to use heat treatment to improve the 2195 aluminum-lithium alloy (initial phase composition is θ′ phase, δ′ phase and β′ phase, density is 2.7 g / cm 3 ) Room temperature tensile properties of the plate (tensile strength is 597.9MPa, elongation is 7.46%). After solution treatment of 2195 aluminum-lithium alloy plate, the tensile strength is significantly reduced and the elongation is significantly increased. For example, when the solution treatment is 510℃ / 35min, the elongation of the alloy plate is 19.05%, which is 155.36% higher than that of the original plate; the tensile strength is 302.43MPa, which is 49.42% lower than that of the original plate. This shows that solution treatment can improve the plasticity of the alloy, but at the expense of strength. After different aging treatments, the tensile strength of 2195 aluminum-lithium alloy is between 500-600MPa, but the elongation is significantly reduced and the reduction effect is more obvious with the increase of aging time. When the heat treatment process is solution treatment (510℃ / 35min) + aging treatment (180℃ / 18h), the alloy obtains a maximum elongation of 10.06%, which is 34.85% higher than that of the original plate; its tensile strength is 523.87MPa, which is 12.38% lower than that of the original plate.
[0006] In summary, the existing technology still has the following problems: 1. The composition and content of 2195 aluminum-lithium alloy are relatively complex, and the types and contents of high-density elements are relatively high, which cannot meet the needs of lightweighting. 2. The plasticity of 2195 aluminum-lithium alloy is improved to a certain extent by heat treatment, but at the expense of high strength. 3. The main strengthening mechanism of 2195 aluminum-lithium alloy in the solid solution + aging process is precipitation strengthening and dispersion strengthening produced by the precipitation of θ′ phase and δ′ phase. There is no equilibrium phase T1 phase with more obvious strengthening effect, which ultimately leads to poor strength-plasticity matching. 4. Due to the poor forming performance of aluminum-lithium alloy itself, the application direction is still in the simple weight reduction of low-density, high-strength lightweight materials. There is still a lack of research on the preparation and processing technology of large-size aluminum-lithium alloy plates with high requirements for comprehensive performance matching. Summary of the invention
[0007] In view of this, the present invention provides an aluminum-lithium alloy and a preparation method thereof. The aluminum-lithium alloy provided by the present invention can achieve good lightness, while also improving strength and obtaining good mechanical properties.
[0008] The present invention also provides an aluminum-lithium alloy, which comprises the following components in percentage by mass: Cu: 2.5%~3.2%; Li: 1.7%~2.2%; Sc: 0.2%~0.3%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.13~1.88.
[0009] The present invention also provides a method for preparing the aluminum-lithium alloy described in the above technical solution, comprising the following steps: A) Prepare ingredients according to the target alloy composition; in, In terms of mass percentage, the target alloy includes the following components: Cu: 2.5%~3.2%; Li: 1.7%~2.2%; Sc: 0.2%~0.3%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.13~1.88; The raw materials used in the batching include: aluminum ingot, metal Cu, metal Li and master alloy Al-2Sc; B) Furnace gas washing: The smelting furnace is evacuated, and inert gas is filled in after the vacuum degree is less than the target threshold. When the pressure in the furnace reaches the target pressure, the filling is stopped and the furnace is left to stand; then, the above-mentioned gas washing process is repeated; C) Vacuum Melting: The aluminum ingot is placed in a container and kept warm in a melting furnace preheated to 760°C until the aluminum ingot is completely melted; then, the temperature is raised to 950°C, metal Cu and master alloy Al-2Sc are added to the molten aluminum liquid, a covering agent is added for covering protection, and the temperature is kept warm until the metal Cu is completely melted; then, the temperature is lowered to 740°C, a covering agent is applied on the surface of the melt, and metal Li is placed in the melt under a protective atmosphere and allowed to stand; thereafter, the melt is stirred to obtain a uniform melt; D) Casting: The casting mold is placed in a preheated smelting furnace for degassing; the container containing the melt obtained in step C) is taken out from the smelting furnace, the slag and surface oxides of the melt are skimmed off, and then the melt is poured into the casting mold. After the casting is completed, the melt is cooled and formed to obtain an ingot; E) performing a homogenization treatment on the ingot; F) hot rolling the alloy obtained in step E); G) The alloy obtained in step F) is subjected to solution treatment and aging treatment in sequence to obtain an aluminum-lithium alloy.
[0010] Preferably, in step C): The holding time until the aluminum ingot is completely melted is 30 minutes; The holding time for holding until the metal Cu is completely melted is 2 hours; The standing time is 20 min.
[0011] Preferably, in step D), the degassing is ammonia degassing.
[0012] Preferably, in step E), the conditions for the homogenization treatment are as follows: The heating rate was 5°C / min, the homogenization temperature was 480°C, and the holding time was 16h; then the furnace was cooled.
[0013] Preferably, in step F), the hot rolling process is three-pass rolling; The rolling temperature is 480°C, and each pass is kept warm for 10 minutes during the rolling process.
[0014] Preferably, in step G), the conditions of the solution treatment are as follows: temperature is 500° C., holding time is 2 h; followed by water quenching.
[0015] Preferably, in step G), the conditions of the aging treatment are as follows: the temperature is 190-210° C., and the insulation time is 22-40 hours.
[0016] Preferably, in step F), the final total deformation of the hot rolling treatment is 60%.
[0017] Preferably, the purity of the aluminum ingot is ≥99.8%, the purity of the metal Cu is ≥99.9%, and the purity of the metal Li is ≥99.9%.
[0018] The present invention provides an aluminum-lithium alloy, which is an ultra-light aluminum-lithium alloy with Sc added. The composition is reasonably designed, rare earth element Sc is used to replace Zr and the Sc element content is controlled, thereby controlling the strengthening phase in the alloy, achieving lightweight, and at the same time, a large amount of dispersedly distributed δ′ phase, T1 phase and second phase particle Al3Sc phase are precipitated from the alloy through homogenization treatment → hot rolling → solid solution + aging, thereby obtaining an ultra-light aluminum-lithium alloy material with good strength and plasticity. The preparation method of the present invention realizes the control of the morphology and size of the precipitated phase T1 (Al2CuLi), and the heat treatment process realizes the regulation of the grain structure morphology, thereby obtaining good mechanical properties.
[0019] The experimental results show that the density of the aluminum-lithium alloy obtained by the present invention is 2.47 g / cm 2 The room temperature tensile strength is above 528 MPa, achieving lightweight and excellent mechanical properties. Among them, the density of the preferred alloy Al-3Cu-1.7Li-0.3Sc is 2.47 g / cm 2 The room temperature tensile strength reaches 554MPa, the elongation is 10.84%, and the comprehensive performance is the best. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0021] Figure 1 EBSD image of the Al-3Cu-1.7Li-0.3Sc ultra-light aluminum-lithium alloy obtained in Example 1; Figure 2 This is the TEM image of the Al-3Cu-1.7Li-0.3Sc ultra-light aluminum-lithium alloy obtained in Example 1. DETAILED DESCRIPTION
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0023] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0024] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0025] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0026] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 190~210℃ means that the units of the left endpoint "190" and the right endpoint "210" are both ℃.
[0027] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0028] The present invention provides an aluminum-lithium alloy, which comprises the following components in terms of mass percentage: Cu: 2.5%~3.2%; Li: 1.7%~2.2%; Sc: 0.2%~0.3%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.13~1.88.
[0029] In the present invention, the content of Cu in the aluminum-lithium alloy is 2.5% to 3.2%, specifically 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, and 3.2%.
[0030] In the present invention, the content of Li in the aluminum-lithium alloy is 1.7% to 2.2%, specifically 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, and 2.2%.
[0031] In the present invention, the content of Sc in the aluminum-lithium alloy is 0.2% to 0.3%, specifically 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, and 0.30%.
[0032] In the present invention, the mass ratio of Cu / Li is 1.13 to 1.88, specifically 1.13, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.47, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.88. The present invention controls w(Cu) / w(Li) within the above range, which is conducive to obtaining the best precipitation phase composition and strengthening the matrix. If the ratio is too low, it is easy to lead to a higher δ′ phase ratio. If the ratio is too high, it is easy to lead to an increase in the segregation of Cu atoms, there is obvious enrichment of Cu elements, and the number of Li-containing strengthening phase T1 phases is reduced, and the matrix cannot be effectively strengthened.
[0033] In one embodiment of the present invention, the composition of the aluminum-lithium alloy is as follows: Cu: 3.0%; Li: 1.7%; Sc: 0.30%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.88.
[0034] In another embodiment of the present invention, the composition of the aluminum-lithium alloy is as follows: Cu: 2.5%; Li: 1.7%; Sc: 0.25%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.47.
[0035] In another embodiment of the present invention, the composition of the aluminum-lithium alloy is as follows: Cu: 2.9%; Li: 2.0%; Sc: 0.30%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.45.
[0036] In another embodiment of the present invention, the composition of the aluminum-lithium alloy is as follows: Cu: 2.5%; Li: 2.2%; Sc: 0.30%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.13.
[0037] The present invention also provides a method for preparing the aluminum-lithium alloy described in the above technical solution, comprising the following steps: A) Prepare ingredients according to the target alloy composition; in, In terms of mass percentage, the target alloy includes the following components: Cu: 2.5%~3.2%; Li: 1.7%~2.2%; Sc: 0.2%~0.3%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.13~1.88; The raw materials used in the batching include: aluminum ingot, metal Cu, metal Li and master alloy Al-2Sc; B) Furnace gas washing: The smelting furnace is evacuated, and inert gas is filled in after the vacuum degree is less than the target threshold. When the pressure in the furnace reaches the target pressure, the filling is stopped and the furnace is left to stand; then, the above-mentioned gas washing process is repeated; C) Vacuum Melting: The aluminum ingot is placed in a container and kept warm in a melting furnace preheated to 760°C until the aluminum ingot is completely melted; then, the temperature is raised to 950°C, metal Cu and master alloy Al-2Sc are added to the molten aluminum liquid, a covering agent is added for covering protection, and the temperature is kept warm until the metal Cu is completely melted; then, the temperature is lowered to 740°C, a covering agent is applied on the surface of the melt, and metal Li is placed in the melt under a protective atmosphere and allowed to stand; thereafter, the melt is stirred to obtain a uniform melt; D) Casting: The casting mold is placed in a preheated smelting furnace for degassing; the container containing the melt obtained in step C) is taken out from the smelting furnace, the slag and surface oxides of the melt are skimmed off, and then the melt is poured into the casting mold. After the casting is completed, the melt is cooled and formed to obtain an ingot; E) performing a homogenization treatment on the ingot; F) hot rolling the alloy obtained in step E); G) The alloy obtained in step F) is subjected to solution treatment and aging treatment in sequence to obtain an aluminum-lithium alloy.
[0038] [About Step A]: A) Prepare the alloy according to the target alloy composition.
[0039] In the present invention, the composition of the target alloy is consistent with that described in the above technical solution, and will not be described in detail here.
[0040] In the present invention, the raw materials used in the batching include: aluminum ingot, metal Cu, metal Li and intermediate alloy Al-2Sc. Among them, the aluminum ingot is industrial pure Al, and its purity is ≥99.8%. The metal Cu is industrial pure Cu, and its purity is ≥99.9%. The metal Li is a high-purity Li block, and its purity is ≥99.9%. The present invention has no special restrictions on the sources of the above raw materials, and they can be commercial products. According to the composition of the target alloy, the mass of the above raw materials required is calculated and cut and matched as the matrix raw material.
[0041] [About step B]: B) Furnace cleaning: Evacuate the smelting furnace, fill it with inert gas after the vacuum degree is less than the target threshold, stop filling when the pressure in the furnace reaches the target pressure, and let it stand; then, repeat the above cleaning process.
[0042] In the present invention, the smelting furnace is not particularly limited and can be any conventional smelting furnace in the art, such as a vacuum resistance furnace. First, the smelting furnace is evacuated, and inert gas is filled in after the vacuum degree is less than the target threshold. When the pressure in the furnace reaches the target pressure, the filling is stopped and the furnace is left to stand. This is a gas washing process. The target threshold is preferably 9.9×10 -3 Pa. The inert gas is preferably argon. The purity of the argon is preferably 99.9%. The target pressure is preferably -0.07 MPa. The standing time is preferably 15 min.
[0043] After the first gas washing process is completed, the gas washing process is preferably repeated to perform a second vacuum washing operation, and then the gas washing process is repeated again to perform a third vacuum washing operation; that is, preferably a total of 3 vacuum washing operations are performed. After the gas washing is completed, vacuum is drawn to make the vacuum degree in the furnace reach the above target threshold, and vacuum melting is performed under this vacuum degree condition.
[0044] [About Step C]: C) Vacuum melting: Place the aluminum ingot in a container and keep it warm in a melting furnace preheated to 760°C until the aluminum ingot is completely melted; then, raise the temperature to 950°C, add metal Cu and intermediate alloy Al-2Sc to the molten aluminum liquid, add a covering agent for covering protection, and keep warm until the metal Cu is completely melted; then, cool down to 740°C, apply a covering agent on the surface of the melt, put metal Li into the melt under a protective atmosphere, and let it stand; then, stir it to obtain a uniform melt.
[0045] in: The container is preferably a crucible. The melting furnace is preheated to 760°C in advance, and the aluminum ingot is placed in the furnace and kept warm until it is completely melted. The holding time is preferably 30 minutes, and the above holding time can fully melt the aluminum ingot.
[0046] After the aluminum ingot is melted to form aluminum liquid, the temperature is raised to 950°C, and metal Cu and intermediate alloy Al-2Sc are added to the molten aluminum liquid. In the present invention, the method of adding is preferably to use a bell jar coated with BN to press the aluminum foil ball wrapped with metal Cu and intermediate alloy Al-2Sc into the molten aluminum liquid. Among them, the aluminum foil ball wrapped with metal Cu and intermediate alloy Al-2Sc can be an aluminum foil ball wrapped with metal Cu and an aluminum foil ball wrapped with intermediate alloy Al-2Sc, or an aluminum foil ball wrapped with metal Cu and intermediate alloy Al-2Sc at the same time. After adding metal Cu and intermediate alloy Al-2Sc, a covering agent is added for covering protection; the covering agent is sprinkled on the surface of the aluminum liquid and can quickly melt to form a covering layer to play a covering and protective role. Among them, the covering agent is preferably potassium chloride, sodium chloride, lithium chloride, lithium fluoride, sodium bisulfate and sodium fluorosilicate. In the above-mentioned covering agent, the mass ratio of potassium chloride, sodium chloride, lithium chloride, lithium fluoride, sodium hydrogen sulfate and sodium fluorosilicate is preferably 1: (0.75-1): (0.175-0.3): (0.05-0.1): (0.025-0.0625): (0.0625-0.15), and in some embodiments it is 1: 1: 0.25: 0.075: 0.05: 0.125. The amount of the covering agent is not particularly limited, and can be used according to the conventional amount in the art, which can be 0.6-1 kg / m 2 Melt, specifically 0.6 kg / m 2 Melt, 0.7 kg / m 2 Melt, 0.8 kg / m 2 Melt, 0.9 kg / m 2 Melt, 1.0 kg / m 2 After adding the covering agent for covering protection, the metal Cu is kept warm until it is completely melted. The holding time is preferably 2 hours, and the metal Cu can be fully melted after the above holding time.
[0047] After the metal Cu is melted, the temperature is lowered to 740°C, and a covering agent is applied to the surface of the melt. There is no special restriction on the method of applying the covering agent, and it can be a conventional method in the art, that is, a layer of covering agent is evenly sprinkled on the surface of the melt. Among them, the covering agent is preferably potassium chloride, sodium chloride, lithium chloride, lithium fluoride, sodium bisulfate and sodium fluorosilicate. In the above-mentioned covering agent, the mass ratio of potassium chloride, sodium chloride, lithium chloride, lithium fluoride, sodium bisulfate and sodium fluorosilicate is preferably 1: (0.75~1): (0.175~0.3): (0.05~0.1): (0.025~0.0625): (0.0625~0.15), and in some embodiments it is 1: 1: 0.25: 0.075: 0.05: 0.125. There is no special restriction on the amount of the covering agent, and it can be used according to the conventional amount in the art, which can be 0.6~1 kg / m 2 Melt, specifically 0.6 kg / m2 Melt, 0.7 kg / m 2 Melt, 0.8 kg / m 2 Melt, 0.9 kg / m 2 Melt, 1.0 kg / m 2 Melt.
[0048] After the above treatment, metal Li is placed in the melt under a protective atmosphere and allowed to stand. The protective atmosphere is preferably argon. Metal Li is placed in the melt and allowed to stand to melt, and the standing time is preferably 20 minutes. Thereafter, stirring is performed, and the aluminum liquid is continuously stirred to promote uniform and sufficient dissolution of all alloy elements in the aluminum liquid to obtain a uniform melt.
[0049] [About Step D]: D) Casting: placing the casting mold into a preheated smelting furnace for degassing; taking the container containing the melt obtained in step C) out of the smelting furnace, skimming off the slag and surface oxides of the melt, and then pouring the melt into the casting mold. After the casting is completed, the melt is cooled and formed to obtain an ingot.
[0050] In the present invention, the casting mold is preferably a casting mold with a BN coating on the surface. The preheating temperature of the preheated smelting furnace is preferably 650°C. The degassing is preferably ammonia degassing. The degassing time is preferably 5 minutes. Then, the container containing the melt obtained in step C) is taken out from the smelting furnace, and the slag and surface oxides of the melt are skimmed and slag is removed to ensure the safety of the metal casting mold. Then, the melt is slowly and uniformly poured into the casting mold, and after the casting is completed, it is naturally cooled and formed to obtain an ingot.
[0051] [About Step E]: E) performing a homogenization treatment on the ingot.
[0052] In the present invention, the heating rate of the homogenization treatment is preferably 5°C / min. The homogenization temperature of the homogenization treatment is preferably 480°C. The holding time of the homogenization treatment is preferably 16h. After the above homogenization heat treatment, furnace cooling is performed, that is, cooling with the furnace, specifically cooling with the furnace to room temperature.
[0053] [About Step F]: F) The alloy obtained in step E) is subjected to hot rolling.
[0054] In the present invention, the hot rolling treatment is preferably three-pass rolling. The rolling temperature is preferably 480°C. During the rolling process, each pass is kept warm for 10 minutes, that is, after each pass is completed, it is kept warm for 10 minutes before the next pass is rolled. After the above hot rolling treatment, the final total deformation reaches 60%. After the above treatment, a thin plate with a thickness of 2.7 mm is obtained.
[0055] [About step G]: G) The alloy obtained in step F) is subjected to solution treatment and aging treatment in sequence to obtain an aluminum-lithium alloy.
[0056] In the present invention, the temperature of the solution treatment is preferably 500° C. The holding time of the solution treatment is preferably 2 hours. After the solution treatment at the above temperature, water quenching is performed.
[0057] In the present invention, the temperature of the aging treatment is preferably 190-210° C., specifically 190° C., 195° C., 200° C., 205° C., 210° C. The holding time of the aging treatment is preferably 22-40 h, specifically 22 h, 24 h, 26 h, 28 h, 30 h, 32 h, 34 h, 36 h, 38 h, 40 h.
[0058] After the above-mentioned solution treatment + aging treatment, the main strengthening phase composition of the alloy is δ′+T1 phase, and the proportion of T1 phase is greater than that of δ′ phase; there is a dispersed Al3Sc phase, which plays a role of dispersion strengthening and fine grain strengthening on the matrix.
[0059] The present invention provides an aluminum-lithium alloy, which is an ultra-light aluminum-lithium alloy with Sc added. The composition is reasonably designed, rare earth element Sc is used to replace Zr and the Sc element content is controlled, thereby controlling the strengthening phase in the alloy, achieving lightweight, and at the same time, a large amount of dispersedly distributed δ′ phase, T1 phase and second phase particle Al3Sc phase are precipitated from the alloy through homogenization treatment → hot rolling → solid solution + aging, thereby obtaining an ultra-light aluminum-lithium alloy material with good strength and plasticity. The preparation method of the present invention realizes the control of the morphology and size of the precipitated phase T1 (Al2CuLi), and the heat treatment process realizes the regulation of the grain structure morphology, thereby obtaining good mechanical properties.
[0060] The experimental results show that the density of the aluminum-lithium alloy obtained by the present invention is 2.47 g / cm 2 The room temperature tensile strength is above 528 MPa, achieving lightweight and excellent mechanical properties. Among them, the density of the preferred alloy Al-3Cu-1.7Li-0.3Sc is 2.47 g / cm 2 The room temperature tensile strength reaches 554MPa, the elongation is 10.84%, and the comprehensive performance is the best.
[0061] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. In the following examples, the raw materials used are high-purity raw materials, the purity of the aluminum ingot is ≥99.8%, the purity of the metal Cu is ≥99.9%, and the purity of the metal Li is ≥99.9%.
[0062] Example 1 1. Preparation A) The target alloy composition is as follows: Cu 3.0%, Li 1.7%, Sc 0.3%, and the balance is Al and unavoidable impurities. Among them, w(Cu) / w(Li)=1.88.
[0063] The raw materials used include: aluminum ingot, metal Cu, metal Li and intermediate alloy Al-2Sc.
[0064] B) Furnace gas washing: The melting furnace (specifically a vacuum resistance furnace) is evacuated until the vacuum degree is less than 9.9×10 -3 Pa, fill with argon (purity of 99.9%), and stop filling when the pressure in the furnace reaches -0.07MPa, and let it stand for 15 minutes; repeat the above washing process to perform the second vacuum washing operation, and then repeat the above washing process again to perform the third vacuum washing operation. After the washing is completed, vacuumize the furnace to the above 9.9×10 -3 Pa, and subsequent vacuum melting is carried out under this vacuum condition.
[0065] C) Vacuum Melting: Preheat the melting furnace to 760℃, put the aluminum ingot into the crucible in the melting furnace, and keep it warm for 30 minutes until the aluminum ingot is completely melted. Then, heat it to 950℃, use a bell jar coated with BN to press the aluminum foil ball wrapped with metal Cu and master alloy Al-2Sc into the molten aluminum liquid, and evenly sprinkle a layer of covering agent on the surface of the aluminum liquid for covering protection (the covering agent is potassium chloride + sodium chloride + lithium chloride + lithium fluoride + sodium hydrogen sulfate + sodium fluorosilicate, the mass ratio of each component is 1:1:0.25:0.075:0.05:0.125, and the amount of covering agent is 0.8 kg / m 2 Melt), keep warm for 2h until the metal Cu is completely melted. Then, cool down to 740℃, and evenly sprinkle a layer of covering agent on the surface of the melt again (the covering agent is potassium chloride + sodium chloride + lithium chloride + lithium fluoride + sodium hydrogen sulfate + sodium fluorosilicate, the mass ratio of each component is 1:1:0.25:0.075:0.05:0.125, and the amount of covering agent is 0.8 kg / m 2 Melt), under the protection of argon, put the Li block into the melt and let it stand for 20 minutes. After that, stir the aluminum liquid continuously to promote all alloy elements to be evenly and fully dissolved in the aluminum liquid to obtain a uniform melt.
[0066] D) Casting: The mold with BN coating on the surface is placed in a preheated (preheating temperature is 650℃) melting furnace, and ammonia gas degassing is performed for 5 minutes. The crucible containing the melt is taken out of the melting furnace, and the slag and surface oxides of the melt are skimmed and slag is removed to ensure the safety of the metal mold. Then, the melt is slowly and evenly poured into the above mold. After the casting is completed, it is naturally cooled and formed to obtain an ingot.
[0067] E) The ingot is homogenized: the heating rate is 5°C / min, the homogenization temperature is 480°C, the holding time is 16h, and the ingot is cooled to room temperature with the furnace.
[0068] F) Hot rolling treatment: The rolling process was repeated for three times at a temperature of 480°C. During the rolling process, each time the temperature was kept at 10 minutes. The final total deformation reached 60%, and a sheet with a thickness of 2.7 mm was obtained.
[0069] G) Heat treatment: Solution treatment and aging treatment are carried out in sequence, and the conditions are as follows: Solution treatment: solution temperature is 500℃, holding time is 2h, and water quenching is performed.
[0070] Aging treatment: aging temperature 210℃, holding time 22h.
[0071] After the above heat treatment, an Al-3Cu-1.7Li-0.3Sc ultra-light aluminum-lithium alloy is obtained.
[0072] 2. Test: (1) EBSD and TEM characterization Example 1 The EBSD of the Al-3Cu-1.7Li-0.3Sc ultra-light aluminum-lithium alloy obtained is as follows: Figure 1 As shown, it can be seen that the grain orientation tends to <001> and <101> , and a large number of small-angle grain boundaries (2°-10°) were formed.
[0073] Example 1 The TEM of the Al-3Cu-1.7Li-0.3Sc ultra-light aluminum-lithium alloy obtained is as follows Figure 2 As shown, it can be seen that the aging precipitation phases are mainly dispersed θ′ phase and needle-shaped T1 phase, the T1 phase content is higher than the θ′ phase content, and there are dispersed Al3Sc phase and a large number of dislocation entanglements.
[0074] (2) Mechanical properties test The density test was carried out using the Archimedes drainage method. Each alloy sample was measured 3 times, and the average density was 2.47 g / cm 2 . According to the room temperature mechanical properties test, the tensile strength is 554MPa and the elongation is 10.84%.
[0075] Example 2 1. Preparation The method is implemented according to Example 1, except that the chemical composition and heat treatment process are different.
[0076] The chemical composition is: Cu 2.5%, Li 1.7%, Sc 0.25%, and the balance is Al and inevitable impurities; wherein w(Cu) / w(Li)=1.47. That is, the obtained alloy is Al-2.5Cu-1.7Li-0.25Sc ultra-light aluminum-lithium alloy.
[0077] The heat treatment process is: solution treatment (500℃ / 2h, water quenching) + aging treatment (190℃ / 40h).
[0078] 2. Testing Through the analysis of the alloy microstructure after heat treatment, it was found that the precipitated phase was mainly dispersed θ′ phase and needle-shaped T1 phase. The content of T1 phase was nearly equal to that of θ′ phase. At the same time, the precipitated phase contained Al3Sc phase and dislocation entanglement existed around it.
[0079] The density test was carried out using the Archimedes drainage method. Each alloy sample was measured 3 times, and the average density was 2.4 g / cm 2 The room temperature mechanical properties test showed that the tensile strength was 542MPa and the elongation was 12.67%.
[0080] Example 3 1. Preparation The method is implemented according to Example 1, except that the chemical composition and heat treatment process are different.
[0081] The chemical composition is: Cu 2.9%, Li 2.0%, Sc 0.30%, and the balance is Al and inevitable impurities; wherein w(Cu) / w(Li)=1.45. That is, the obtained alloy is Al-2.9Cu-2Li-0.3Sc ultra-light aluminum-lithium alloy.
[0082] The heat treatment process is: solution treatment (500℃ / 2h, water quenching) + aging treatment (195℃ / 32h).
[0083] 2. Testing Through the analysis of the alloy microstructure after heat treatment, it was found that the precipitated phase was mainly dispersed θ′ phase and needle-shaped T1 phase. The content of T1 phase was slightly less than that of θ′ phase. At the same time, the precipitated phase contained Al3Sc phase and dislocation entanglement existed around it.
[0084] The density test was carried out using the Archimedes drainage method. Each alloy sample was measured 3 times, and the average density was 2.38 g / cm 2 . According to the room temperature mechanical properties test, the tensile strength is 528MPa and the elongation is 12.95%.
[0085] It can be seen from Examples 1-3 that the density of the aluminum-lithium alloy obtained in the present invention is 2.47 g / cm 2 The room temperature tensile strength is above 528 MPa, achieving lightweight while having excellent mechanical properties. Among them, compared with Examples 2-3, the tensile strength of the Al-3Cu-1.7Li-0.3Sc alloy obtained in Example 1 is the best, the experimental time required is the shortest, and its strength-to-plastic ratio is the highest. Therefore, considering the strength-to-plastic ratio and lightweight and cost consumption in practical applications, Example 1 is the best.
[0086] Comparative Example 1 2195 aluminum-lithium alloy after heat treatment in the preparation process proposed by Xing Yuhan et al. (see the article "Effects of Heat Treatment on the Microstructure and Mechanical Properties of 2195 Aluminum-Lithium Alloy").
[0087] Comparing the room temperature tensile test results of Example 1 of the present invention with those of Comparative Example 1, it is found that: the room temperature tensile strength of Comparative Example 1 is 523.87MPa, and the elongation is 10.06%; while the room temperature tensile strength of the Al-3Cu-1.7Li-0.3Sc alloy obtained by the present invention is 554MPa, and the elongation is 10.84%, which is better than the existing alloy. Moreover, the density of the present invention is reduced (Comparative Example 1 is 2.7g / cm 2 , Example 1 is 2.47 g / cm 2 ). Moreover, the Al-3Cu-1.7Li-0.3Sc alloy obtained by the present invention has an excellent strength-to-plasticity ratio at room temperature and is suitable for being put into the field of industrial production.
[0088] The present invention provides an ultra-light aluminum-lithium alloy with added Sc. By rationally designing the component composition, controlling the preparation process and the solid solution + aging system, the mechanical properties and the second phase precipitation behavior of the ultra-light aluminum-lithium alloy are regulated, which has positive guiding significance for the performance improvement and industrial application of new aluminum-lithium alloys.
[0089] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. An aluminum-lithium alloy, characterized in that: In terms of mass percentage, it includes the following ingredients: Cu: 2.5%~3.2%; Li: 1.7%~2.2%; Sc: 0.2%~0.3%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.13~1.
88.
2. A method for preparing the aluminum-lithium alloy according to claim 1, characterized in that: The following steps are involved: A) Prepare ingredients according to the target alloy composition; in, In terms of mass percentage, the target alloy includes the following components: Cu: 2.5%~3.2%; Li: 1.7%~2.2%; Sc: 0.2%~0.3%; Al and unavoidable impurities: balance; Among them, the mass ratio of Cu / Li is 1.13~1.88; The raw materials used in the batching include: aluminum ingot, metal Cu, metal Li and master alloy Al-2Sc; B) Furnace gas washing: The smelting furnace is evacuated, and inert gas is filled in after the vacuum degree is less than the target threshold. When the pressure in the furnace reaches the target pressure, the filling is stopped and the furnace is left to stand; then, the above-mentioned gas washing process is repeated; C) Vacuum Melting: The aluminum ingot is placed in a container and kept warm in a melting furnace preheated to 760°C until the aluminum ingot is completely melted; then, the temperature is raised to 950°C, metal Cu and master alloy Al-2Sc are added to the molten aluminum liquid, a covering agent is added for covering protection, and the temperature is kept warm until the metal Cu is completely melted; then, the temperature is lowered to 740°C, a covering agent is applied on the surface of the melt, and metal Li is placed in the melt under a protective atmosphere and allowed to stand; thereafter, the melt is stirred to obtain a uniform melt; D) Casting: The casting mold is placed in a preheated smelting furnace for degassing; the container containing the melt obtained in step C) is taken out from the smelting furnace, the slag and surface oxides of the melt are skimmed off, and then the melt is poured into the casting mold. After the casting is completed, the melt is cooled and formed to obtain an ingot; E) performing a homogenization treatment on the ingot; F) hot rolling the alloy obtained in step E); G) The alloy obtained in step F) is subjected to solution treatment and aging treatment in sequence to obtain an aluminum-lithium alloy.
3. The preparation method according to claim 2, characterized in that: In step C): The holding time until the aluminum ingot is completely melted is 30 minutes; The holding time for holding until the metal Cu is completely melted is 2 hours; The standing time is 20 min.
4. The preparation method according to claim 2, characterized in that: In step D), the degassing is ammonia degassing.
5. The preparation method according to claim 2, characterized in that: In step E), the homogenization conditions are as follows: The heating rate was 5°C / min, the homogenization temperature was 480°C, and the holding time was 16h; then the furnace was cooled.
6. The preparation method according to claim 2, characterized in that: In step F), the hot rolling process is three-pass rolling; The rolling temperature is 480°C, and each pass is kept warm for 10 minutes during the rolling process.
7. The preparation method according to claim 2, characterized in that: In step G), the conditions of the solution treatment are as follows: temperature is 500° C., holding time is 2 h; followed by water quenching.
8. The preparation method according to claim 2, characterized in that: In step G), the aging treatment conditions are as follows: temperature is 190-210° C., and the insulation time is 22-40 hours.
9. The preparation method according to claim 2 or 6, characterized in that: In step F), the final total deformation amount of the hot rolling treatment is 60%.
10. The preparation method according to claim 2, characterized in that: The purity of the aluminum ingot is ≥99.8%, the purity of the metal Cu is ≥99.9%, and the purity of the metal Li is ≥99.9%.
Citation Information
Patent Citations
Thermal treatment process for improving corrosion resistance of aluminum-lithium alloy
CN106521270A
Heat-resistant aluminum-lithium alloy and preparation method thereof
CN110423926A
Silver-free high-strength anti-fatigue aluminum lithium alloy and preparation and heat treatment method thereof
CN118086736A
High-strength particle reinforced aluminum-lithium-based alloy and preparation process and application thereof
CN119351836A
High-strength and high-toughness aluminum-lithium alloy as well as preparation method and application thereof
CN119433294A